Carotid artery corrected flow time and respiratory variation of blood flow peak velocity for prediction of hypotension after induction of general anesthesia in adult patients undergoing emergency laparotomy for peritonitis: A prospective, observational study - Apala R Chowdhury; Ruma Thakuria; Souvik Maitra; Sayan Nath; Dalim K Baidya; Rajeshwari Subramanium; Rahul K Anand; Choro A Kayina (Journal of Anaesthesiology Clinical Pharmacology, 2023)
Background and Aims: Doppler waveform analysis of carotid artery has been found to predict fluid responsiveness in patients undergoing elective surgeries. We evaluated the role of carotid artery corrected flow time (FTc) and respiratory variation of blood flow peak velocity (ðVpeak) in predicting post induction hypotension in patients undergoing emergency laparotomy for peritonitis. Material and Methods: Adult patients (n = 60) with perforation peritonitis undergoing emergency laparotomy under general anesthesia (GA) were recruited in this prospective, observational study. Carotid ultrasonography was performed pre-induction, to determine FTc and ðVpeak. Post-induction hemodynamic parameters were recorded for 5 minutes. Spearman's rank correlation coefficient was used to determine the relationship between hypotension and carotid artery measurements. Results: Post-induction hypotension occurred in 48.3% of patients. The carotid artery FTc was significantly lower (P = 0.008) in patients who developed post-induction hypotension, but ðVpeak was statistically similar (P = 0.62) in both groups. Spearman's rank correlation coefficient revealed a statistically significant correlation between FTc and systolic blood pressure (SBP) change at one-minute post induction (r2 = −0.29, P = 0.03); however statistical significance were not achieved at 2 minutes and 3 minutes (P = 0.05 at both time points). Carotid artery FTc had an area under the receiver operating characteristic (AUROC) curve (95% CI) of 0.70 (0.57–0.84) to predict post-induction hypotension and best cutoff value of 344.8 ms with a sensitivity and specificity of 61% and 79%, respectively. Carotid artery ðVpeak had an AUROC curve (95% CI) of 0.54 (0.39–0.69) to predict post-induction hypotension and best cutoff value of 7.9% with a sensitivity and specificity of 62% and 55%, respectively. Conclusion: Carotid artery FTc and ðVpeak are not reasonable predictors of hypotension in patients undergoing emergency laparotomy for perforation peritonitis.